Medicinal plants used for menstrual regulators and pain relievers in Tumiang Village, West Kalimantan, Indonesia - RUQIAH GANDA PUTRI PANJAITAN; KHAIRUNNISA KHAIRUNNISA; TITIN TITIN; DIAN AKBARINI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Panjaitan RGP, Khairunnisa, Titin, Akbarini D. 2024. Medicinal plants used for menstrual regulators and pain relievers in Tumiang Village, West Kalimantan, Indonesia. Biodiversitas 25: 4796-4805. The use of medicinal plants for traditional treatment is a common practice in various rural areas in Indonesia. Therefore, this study aims to create an inventory of medicinal plants used as menstrual regulators and pain relievers by the community in Tumiang Village, Samalantan Sub-district, Bengkayang District, West Kalimantan, Indonesia. This study employs a qualitative method with triangulation techniques, and data collection was conducted with interviews, observations, and documentation by involving 11 informants. The results showed that a total of 15 plants were used as menstrual regulators and pain relievers by the community of Tumiang Village. These included korongan (Ricinus communis), marampayo (Croton hirtus), kakompo (Limnophila rugosa), sarat saribu (Lygodium microphyllum), antidur (Phyllanthus urinaria), ganda rusa (Phaleria macrocarpa), ahiak (Zingiber officinale), cakur (Kaempferia galanga), unyit (Curcuma longa), tamulawak (Curcuma zanthorrhiza), matsoe (Perilla frutescens), karaoke (Piper betle), kumis kucing (Orthosiphon aristatus), asam jawa (Tamarindus indica), and rosella (Hibiscus sabdariffa). In addition, 2 plants, namely pinang (Areca catechu) and saring kuyang (Zingiber purpureum), were specifically used only as menstrual pain relievers. The results of the study highlight the unique role of the Zingiberaceae family is the most commonly utilized, with leaves being the most frequently used plant part, and the most prevalent processing method being boiling. This research underscores the significance of these plants in the health of the local community and their potential for further scientific exploration.